EFFECT SELF ASSESSMENT IMPLEMENTATION, TAXATION SOCIALIZATION, TAXATION SANCTION AND SERVICE QUALITY OF TAX AUTHORITIESTO COMPLIANCE LEVEL OF TAXPAYER OF MSMES PERPETRATORS AFTER IMPLEMENTATION OF GOVERNMENT REGULATION NO. 46 YEAR 2013 - Suhendra Suhendra; Asep Kurniawan; Asri Suangga (Journal of Taxation Analysis and Review, 2019)
This research aimed to know the effect ofSelf AssessmentImplementation, Taxation Socialization, Taxation Sanction And Service quality tax authoritiesTo Taxpayer Compliance Level. The population in this research wase of Taxpayers of MSMEsperpetrators of trade centers. The data used were ordinal data were transformed using the MSI. The research method was descriptive analysis method with quantitative approach. The statistical method was multiple linear regression analysis, the coefficient of determination, t-test, F-test, by using SPSS for windows. The results of the research indicate that variableSelf AssessmentImplementation proved to have a positive influenceand significant effect on tax compliance rate variable, variable Taxation Socialization not proven to have a positive influence and significant effect on tax compliance rate variable, variable Taxation Sanction proved to have a positive influence and significant effect on tax compliance rate variable, variable Service quality tax authoritiesto have a positive influence and significant effect on tax compliance rate variable,and variable Self Assessmentimplementation, Taxation Socialization, Taxation Sanction And Service quality tax authoritiesto have a positive influence simultaneously and significant effect on tax compliance rate variable.